Gene silencing of stearoyl-ACP desaturase enhances the stearic acid content in Chlamydomonas reinhardtii. (December 2017) - de Jaeger, L.; Springer, J.; Wolbert, E.J.H.; Martens, D.E.; Eggink, G.; Wijffels, R.H.
Highlights: Stearoyl-ACP desaturase is silenced by artificial microRNA in the green microalga Chlamydomonas reinhardtii . Increased stearic acid content in triacylglycerol molecules in mutants of Chlamydomonas reinhardtii . Temperature impacts the accumulation rate of stearic acid. Abstract: In this study, stearoyl-ACP desaturase (SAD), the enzyme that converts stearic acid into oleic acid, is silenced by artificial microRNA in the green microalga Chlamydomonas reinhardtii . Two different constructs, which target different positions on the mRNA of stearoyl-ACP desaturase, were tested. The mRNA levels for SAD were reduced after the silencing construct was induced. In one of the strains, the reduction in SAD mRNA resulted in a doubling of the stearic acid content in triacylglycerol molecules, which shows that stearic acid production in microalgae is possible.